A one-dimensional model of a jet-ejector in critical double choking operation with R134a as a refrigerant including real gas effects. (July 2015) - Zegenhagen, M.T.; Ziegler, F.
Abstract: The geometrical simplicity of a jet-ejector is in stark contrast to the complexity of the flow phenomena occurring in ejector operation. The available flow models range from empirical models to models based on computational fluid dynamics, differing considerably in complexity and thus explanatory power. The one-dimensional flow models of semi-empirical nature are based on experiments at comparatively low motive pressures and thus on ideal gas equations. In contrast, a one-dimensional, experimentally validated model of a jet-ejector in critical double choking operation which includes real gas effects and relies on a single physically interpretable loss coefficient is introduced in the present paper. Real gas effects impact on the state quantities and the critical mass flow of the expansion in the supersonic nozzle in particular which should be considered in the determination of the entrainment ratio or the absolute motive and suction mass flows of the ejector and in ejector design. Highlights: Deduction of real gas equations and approximations needed for jet-ejector modeling. Introduction of a physical one-dimensional jet-ejector model including real gas effects. Simulation of experiments of critical jet-ejector double choking operation. Introduction of a physically interpretable loss coefficient based on experiments. Analysis of the real gas effects and comparison of simulation and experiments.